2018
DOI: 10.1039/c8ib00103k
|View full text |Cite|
|
Sign up to set email alerts
|

Directed evolution of excited state lifetime and brightness in FusionRed using a microfluidic sorter

Abstract: Green fluorescent proteins (GFP) and their blue, cyan and red counterparts offer unprecedented advantages as biological markers owing to their genetic encodability and straightforward expression in different organisms. Although significant advancements have been made towards engineering the key photo-physical properties of red fluorescent proteins (RFPs), they continue to perform sub-optimally relative to GFP variants. Advanced engineering strategies are needed for further evolution of RFPs in the pursuit of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 43 publications
1
60
0
Order By: Relevance
“…Four positions near the phenol end of the chromophore-C159, M161, V196 and H198-were simultaneously mutated in FR to generate a ~7,000-member library (See Methods and Materials for details of library generation). We employed lifetime-based microfluidic flow cytometry 35 to select variants with increased brightness and values of  different from the parent (Figure 1). Sequencing of selected clones revealed that H198 and V196 were conserved but positions 159 and 161 showed sequence diversity (Supplementary Information S2: Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four positions near the phenol end of the chromophore-C159, M161, V196 and H198-were simultaneously mutated in FR to generate a ~7,000-member library (See Methods and Materials for details of library generation). We employed lifetime-based microfluidic flow cytometry 35 to select variants with increased brightness and values of  different from the parent (Figure 1). Sequencing of selected clones revealed that H198 and V196 were conserved but positions 159 and 161 showed sequence diversity (Supplementary Information S2: Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Library Targets: We targeted the positions 159, 161, 196 and 198 in FR (using FR numbering; Supplementary Information S1), expressed the libraries in yeast (Sacchromyces cerevisiae) and screened this library on a lifetime flow cytometer. 35 Screening revealed the presence of brighter clones with longer and shorter lifetime than parent FR (lifetime ~ 2.05 ns). We performed another two rounds of FACS enrichment on a BD FACSAria Fusion Cell Sorter to remove the dim/non-fluorescent clones.…”
Section: Microfluidic Based Selection From Site Directed Librariesmentioning
confidence: 99%
See 3 more Smart Citations